(untitled) (Texas Journal of Medical Science, 2022)
The current study aims to show the importance of leadership qualities of the professors of the College of Physical Education and Sports Sciences at Tikrit University. The problem of the research lies in preparing educational leaders in a way that suits the changing conditions and interacts with them. It is unreasonable to wait for educational leaders who live with their traditional ideas to prepare for us a generation that is abreast with modern technological and scientific developments unless we prepare them in a proper way that put them in a balanced line with those developments. Hence, the research problem lies in studying the leadership qualities of teachers in the College of Physical Education and Sports Sciences from the point of view of their students. As for the research sample, it included students of the College of Physical Education and Sports Sciences / Tikrit University, as they were selected from four-year students of the college. The researcher used the questionnaire as a research tool to collect data and information related to the subject of the research. It consists of a set of various questions and inquiries that are related to each other in a way that achieves the goal that the researcher seeks to address in the light of his subject and the problem he has chosen for his research. Responses with a high statistical significance for students towards the leadership qualities of the teachers of the College of Physical Education and Sports Sciences / Tikrit University.